Meningkatkan Pelayanan Administrasi Publik di Indonesia - Rita Komalasari; Nurhayati; Cecep Mustafa (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
This paper presents the findings to improve public administration services. For the first time, the findings presented in this paper contribute to knowledge and to addressing problems, as well as to provide direct and tangible benefits to the service of the wider community. The research method presented in this paper is a qualitative study involving interviews with participants who are District Court Judges and observations in two selected courts. The findings presented in this paper will have an impact on improving services administration in the public sector in Indonesia.